Trends in Acarology 2010
DOI: 10.1007/978-90-481-9837-5_77
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide side-effects on predatory mites: the role of trophic interactions

Abstract: 465The control of spider mites in protected crops is often critical due to the development of mite resistance to acaricides. Studies of the side-effects of pesticides on beneficial mites are required in order to improve integrated spider mite management. Pesticide side-effects on predatory mites of the family Phytoseiidae can be studied at the field or laboratory level. In the field, phytoseiid abundance can be related to the presence of prey and/or alternative foods, which can affect the response of predatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…In contrast, the total effect of all concentrations of fenpyroximate, and field, as well as, one half the field concentration of abamectin were found toxic to predatory mite and above upper threshold. The overall results confirmed that P. persimilis is promise and crucial to develop IPM programs in agricultural crops; similar results were obtained by (Cloyd et al 2006, Pozzebon & Duso 2010.…”
Section: Side Effects On Predatory Mitessupporting
confidence: 86%
“…In contrast, the total effect of all concentrations of fenpyroximate, and field, as well as, one half the field concentration of abamectin were found toxic to predatory mite and above upper threshold. The overall results confirmed that P. persimilis is promise and crucial to develop IPM programs in agricultural crops; similar results were obtained by (Cloyd et al 2006, Pozzebon & Duso 2010.…”
Section: Side Effects On Predatory Mitessupporting
confidence: 86%
“…The studies reported susceptibility with slight to moderate virulence to P. persimilis after observation periods of three days (Duso et al 2008), six days (Pozzebon and Duso 2010) and 12 days (Numa Vergel et al 2011). Only Ludwig and Oetting (2001) reported high virulence to P. persimilis exposed to topical treatment of B. bassiana with 100 % mortality, although time of death and sporulation was not mentioned.…”
Section: Discussionmentioning
confidence: 99%
“…Offspring of arthropods infected with B. bassiana may exhibit reduced survival and fecundity, moulting problems and malformations (Torrado-Leon et al 2006). Egg hatching success can be significantly reduced for gravid B. bassiana-treated N. californicus (Castagnoli et al 2005) and P. persimilis (Pozzebon and Duso 2010), but, contrary to these findings, treatment of P. persimilis with B. bassiana has also been reported to have no effect on egg hatching success (Duso et al 2008;Seiedy et al 2012). The results of the current study are consistent with the latter: no significant effect was observed on egg viability, juvenile survival or the sex ratio of offspring from B. bassiana-treated A. swirskii.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations